Catalytic conversion of toluene as a biomass tar model compound using monolithic biochar-based catalysts decorated with carbon nanotubes and graphic carbon covered Co-Ni alloy nanoparticles. (15th September 2022) - Tian, Beile; Dong, Kaiming; Guo, Feiqiang; Mao, Songbo; Bai, Jiaming; Shu, Rui; Qian, Lin; Liu, Qi
Graphical abstract: Highlights: Monolithic biochar-based catalysts decorated with graphitic carbon were synthesized. The biological structure of pinewood was preserved with regular 20–40 μm channels. High-density metal or alloy NPs were encapsulated on the wall of the channels. The catalysts showed high activity and excellent stability in toluene reforming. Abstract: Biomass materials forms special biological structures in their growth process, and these structures can be well retained via thermochemical conversion, which have great potential to be used as a porous support for the preparation of high-performance catalysts. In this paper, the monolithic biochar-based catalysts with unique long and through micro channels decorated with graphitic carbon covered metal nanoparticles were synthesized through hydrothermal combined carbonization and evaluated in toluene cracking and steam reforming to evaluate their potential in biomass tar decomposition. The as-prepared catalysts inherited the pore structure of the biomass material, showing neatly arranged channels with a diameter of around 20–40 μm, which can act as flow-through microreactors for the toluene reforming. Co, Ni and Co-Ni alloy nanoparticles were formed on the surface of the channels and anchored by graphitic carbon layers, providing abundant and stable active sites for the catalytic reaction. The Ni-Co alloy nanoparticles achieved the synergistic effect of Co and Ni, and the corresponding catalysts (PC@CoNi/GC) exhibited higher performance and better stability than the catalysts with pure Co and Ni nanoparticles. By using PC@CoNi/GC as the catalyst, the toluene conversion reached 95.51% for the toluene cracking and 100% for the toluene steam reforming at 700 °C, and maintained excellent stability during long-term continuous operation of 2 h and 9 h, respectively. H2 and CO were the main products with a small amount of CO2 and CH4 . Carbon nanotubes were uniformly grown during the toluene reforming process, which may strengthen the adsorption and disturbance of reactants, thus ensuring the stability and activity of PC@CoNi/GC.